Adult attachment insecurity and dyadic adjustment: The mediating role of self-criticism - Martins, Teresa C. (2015)
Although it is well established that adult attachment is associated with relationship quality, the mechanisms involved in this association are still poorly understood. Individual variables that are shaped in early attachment experiences, such as self-criticism, may be particularly important. The present study aimed to investigate the mediating role of self-criticism and self-reassurance on the association between attachment-related anxiety and avoidance and dyadic adjustment.